Domanda, produttività e dinamica occupazionale: un'analisi per "moltiplicatori" applicata a sette paesi OECD, 1960-1995 - Paolo Piacentini; Paolo Pini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
– The paper proposes a quantitative assessment of the impact of demand side factors, i.e. growth, composition and distribution of income, in the determination of changes in the aggregate balance of employment. The level of employment warranted in a system is here derived from the application of a simple scheme which we have called, following the seminal contribution of Richard Kahn in 1931, the "employment multiplier". Starting from an accounting identity between the values of aggregate supply and demand, a level of warranted employment is derived, given the labour coefficient and the deflated values of final demand, in which autonomous components are distinguished from an induced component, this latter depending on total labour income. The variations, over decades and cycles, of aggregate employment for seven OECD countries (France, Italy, Japan, Sweden, United Kingdom, United States and West Germany,), from 1960 onwards, are then analysed and decomposed into the effects of the contributions of three components: growth of average productivity of labour, of "autonomous" demand, and of the "multiplier", a term which summarises the impact of wage share and consumption propensity on induced demand and again on the level of overall employment.
Keywords: 330